Outcome of fracture shaft of humerus fixed with dynamic compression plate in B. P. Koirala Institute of Health Sciences, Dharan, Nepal - Shah Kalawar, Rosan Prasad; Chaudhary, Pashupati (Birat Journal of Health Sciences, 2024)
Introduction: Open reduction and internal fixation with dynamic compression plate (DCP) is necessary for fracture shaft of humerus (SoH) whose closed reduction is not acceptable or cannot be retained in slab or cast. Objectives: Aim of the study was to evaluate outcome of fracture SoH fixed with DCP. Methodology: Patients with fracture SoH fixed with DCP in BPKIHS in 2015-16 were prospectively studied for one year for perioperative issues and functional outcome using DASH score. Results: There were 87 patients of fracture SoH fixed with DCP. Among 87 patients, 65.5% were male and 34.5% were female. The mean age was 36.4 years. The most common mode of injury was road traffic accident followed by fall from height, work place injury. The average operating time was 71 minutes with standard deviation 15.6. The mean blood loss was 205ml ± 45.60. Post-operative hospital mean stay was 4.5 days. There was post-operative radial nerve palsy in 4.6%. Only 69 patients can be followed up for one year for evaluation. Radial nerve palsy recovered fully in those with post-operative palsy. Disability of shoulder arm and hand (DASH) score was 82.50±9.6 after one year of surgery. Fracture was not united in 3(4.3%) patients out of 69 patients who reported for follow up at one year of injury and needed bone grafting and secondary intervention. This shows satisfactory functional outcome in fracture SoH fixed with DCP. Conclusion: Dynamic compression plating for SoH fracture has satisfactory outcome.